European spatial strategies and local development in Central Europe - WILLIAMS, Richard H. (European Spatial Research and Policy, 1995)
This paper argues that development of loca! planning strategies must take into account the recent growth of spatial policy-making at the scale of Europe as a whole. This is especially em1 1hasised in the case of the former communist countries of Central Europe and is illustrated with reference to Poland, the German-Polish border and other parts of the Baltic region. The context of EU enlargement and future integration of Central Europe is outlined to argue the importance in this context of the difference between Central and Eastern Europe. The paper also refers to new powers under the Maastricht Treaty concerning spatial policy, to networking and to the changing spatial structure of Europe.